Cake slicer / Mohd Taufiq Mohd Sharudin ... [et al.] - Mohd Sharudin, Mohd Taufiq; Mohd Suira Affandi, Mohd Imran; Mohd Jalil, Mohd Ermizan; Mohd Jumadi, Asreen Izhar; Sulaiman, Muhammad Hisham (2004)
This 'cake sheer' is built to ease the operation of slicing a cake either for workers at the cake shop of even for home used. It can also be used for birthday parties. The unique design of this 'cake sheer' is to slice the cake rather than a slice at a time, this 'cake sheer' can slice the cake 8 slices at a time. This will reduce the time of slicing the cake and will give a symmetry shape for each slice.